Аспекти актуальності книги як основного виду видання - Зволинська, Леся Я.; Zvolynska, L. Ya. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті висвітлюються аспекти актуальності паперової книги: релігійний, прогресивний, функціональний, культурний, національний, історичний, психологічний, педагогічний, ціннісний, мистецький, стабілізаційний, аспект соціалізації і персоналізації, аспекти сприяння грамотності, виховання культури висловлювання, розвитку мислення та ін. In this article the actuality aspects of the paper book are enlightened namely: the religious aspect (every religion has at its basic the book – primary source (the origin book), at which this religion bases itself as on inviolable authority); the demiurgic aspect (in the book the words which thanks to their «magic» characteristics it seems to man that he can govern the visible and unvisible world, govern and to create are noted); the national, historical aspect (in the book the signs of the nation originality as its language and history are accumulated); the pedagogical, psychological, communication aspects, the aspects of the socialization and personalization, the development of thinking and the culture and literacy moulding aspects and also the progressive, functional, stabilizing, valuable, art aspects.
The actuality aspects of the book as main type of the edition
Keywords: Інтернет; Internet; традиційна й електронна книга; the traditional paper and electronic book; аспекти актуальності; the actuality aspects